MAKING LIQUID SMOKE FOR BIOPESTICIDE FROM SMALL YOUNG COCONUT "BUNGKAK" WASTE IN TAMBAWARAS TEMPLE, TABANAN, BALI. - Sardiana I Ketut; I Wayan Nata Septiadi; Ni Made Witariadi (SWAGATI : Journal of Community Service, 2026)
Tambawaras temple is known as a sacred site for the Balinese ritual of self-purification (melukat). The ritual uses small young coconuts, called "bungkak," as a ritual offering. The increasing number of visitors has triggered a waste problem, as "bungkak" decays over time and is difficult to handle. This community service activity aims to address the problem of small young coconut "bungkak" waste through the application of pyrolysis technology into liquid smoke for biopesticides. The activity consists of several stages, namely: socialization, training, technology application, mentoring, evaluation and follow-up. The results of the activity show that the application of innovation and technology of simple pyrolysis tools has been able to process “bungkak” waste into liquid smoke for biopesticides. Target partners gave a positive response to the implementation of the activity, where 100% of partner members were present and actively participated in the counseling and training. The activity was also able to increase the level of partner empowerment, namely: as many as 80% of partner members have understood the importance of utilizing bungkak waste into liquid smoke for biopesticides. As many as 40% of participants were able and skilled in operating pyrolysis equipment, and as many as 10% were able to turn liquid smoke into biopesticides.